War and peace in Islam a critique of Islamic/ist political discourses - Mirbagheri, Farid (Rethinking peace and conflict studies, 2012)
The question of conflict in Islam has now for sometime been interpreted in the Western diplomatic circles through the violent actions of fundamentalist groups and amongst many academics through a jurisprudential outlook. This work, however, views war and peace in Islam in a critical theoretical framework, in relation to systemic approaches to International Relations. In so doing it relies heavily on the teachings of Islamic mysticism. It suggests that empowering the individual to control him/herself within, as propounded in Sufism and as opposed to systemic approaches, is a prelude to establishing enduring global peace. Without internal tranquility, external harmony will be next to impossible.